Responses of the Internal and External Economic Conditions to Exchange Rate Regimes in Nigeria: The Comparative Analysis - Deekor , Lee Lee N. (Journal of Social Science Studies, 2022)
Exploring the ARDL modeling techniques, this study hypothesized that the internal and external economic conditions respond differently to exchange rate regimes. Covering the period between 1970 and 2020, the study shows that both fixed regime and intermediate regimes have the potential of causing declining inflation (INFL) compared to floating exchange rate regimes. However, when the economic condition is considered from the external perspective measures using trade balance, the magnitude of the impact of both fixed and intermediate regimes appears to be relatively higher for the external economic condition (trade balance) compared to inflation which is a measure for internal economic condition. More importantly, our findings tend to find support in a number of the previous studies.